Ready player two : a novel - Cline, Ernest (Ballantine Books, 2020)
"A 1980s cultural assessment of the fantastical future of online behavior continues the story that began in the internationally best-selling futuristic novel, Ready Player One, that inspired a blockbuster Steven Spielberg film"--